2019
DOI: 10.3171/2017.11.jns171500
|View full text |Cite
|
Sign up to set email alerts
|

Global neurosurgery: the current capacity and deficit in the provision of essential neurosurgical care. Executive Summary of the Global Neurosurgery Initiative at the Program in Global Surgery and Social Change

Abstract: OBJECTIVE Worldwide disparities in the provision of surgical care result in otherwise preventable disability and death. There is a growing need to quantify the global burden of neurosurgical disease specifically, and the workforce necessary to meet this demand. METHODS Results from a multinational collaborative effort to describe the global neurosurgical burden were aggregated and summarized. First, country registries, third-party modeled data, and meta-analyzed published data were combined to generate inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
271
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(272 citation statements)
references
References 17 publications
1
271
0
Order By: Relevance
“…Recently, the team at the Global Neurosurgery Initiative (GNI) of the Program in Global Surgery and Social Change (PGSSC) at Harvard Medical School reported that 5 million emergency and essential neurosurgical operations are unmet each year, requiring 23 300 additional neurosurgeons 5. Further, the WFNS and PGSSC have been able to map the availability of neurosurgical facilities, workforce and essential equipment in a geospatial manner, allowing for visualisation of the areas in critical need.…”
Section: Global Neurosurgerymentioning
confidence: 99%
“…Recently, the team at the Global Neurosurgery Initiative (GNI) of the Program in Global Surgery and Social Change (PGSSC) at Harvard Medical School reported that 5 million emergency and essential neurosurgical operations are unmet each year, requiring 23 300 additional neurosurgeons 5. Further, the WFNS and PGSSC have been able to map the availability of neurosurgical facilities, workforce and essential equipment in a geospatial manner, allowing for visualisation of the areas in critical need.…”
Section: Global Neurosurgerymentioning
confidence: 99%
“…Dewan et al recently reported the estimate of the global volume of neurosurgical diseases, as well as the number and the distribution of neurosurgeons worldwide. 6 They calculated an operative deficit of 5 million neurosurgical cases per annum, with traumatic brain injury, stroke-related conditions, tumors, hydrocephalus, and epilepsy comprising the majority of the global neurosurgical disease burden. 4,5,[7][8][9][10]14,15,18 They further estimated that 23,300 additional neurosurgeons are needed to address the deficit, mostly in Africa and Southeast Asia.…”
Section: Current Capacity and Deficit In Essential Neurosurgical Carementioning
confidence: 99%
“…Every year, 13.8 million patients around the globe require surgery due to traumatic brain injury (TBI), stroke-related conditions, tumors, hydrocephalus, and epilepsy [11]. Millions of these surgical cases are in low-and middle-income countries where acute care is hard to come by.…”
Section: Introductionmentioning
confidence: 99%